Respuesta :

Step-by-step explanation:

1) [tex](-4)^2{\cdot}(-4)[/tex]

We know that, [tex]a^x{\cdot}a^y=a^{x+y}[/tex]

[tex](-4)^2{\cdot}(-4)=(-4)^{2+1}\\\\=(-4)^3\\\\=64[/tex]

2) [tex](-2)^5{\cdot} (-2)^3[/tex]

Again using above property,

[tex](-2)^5{\cdot} (-2)^3=(-2)^8\\\\=256[/tex]

3) [tex]5^{-3}[/tex]

We know that,

[tex]a^{-x}=\dfrac{1}{a^x}[/tex]

So,

[tex]5^{-3}=\dfrac{1}{5^3}\\\\=\dfrac{1}{125}[/tex]

4) [tex]2.5^2=2.5\times 2.5\\\\=6.25[/tex]

Hence, this is the required solution.

ACCESS MORE